Comparative study of CT-guided radiofrequency and alcohol ablation in the treatment of primary hyperhidrosis - Yu, Yaoping; Cui, Jie; Zhang, Yu; Feng, Lei; Wang, Lijun (Frontiers in Surgery, 2024)
Objective: This study compared the efficacy and complications of percutaneous radiofrequency ablation with anhydrous alcohol ablation of sympathetic nerves in treating hyperhidrosis of the head and palms. Methods: A retrospective analysis was conducted on 54 patients with primary hyperhidrosis in our department from June 2018 to June 2021, divided into a radiofrequency ablation group (30 cases) and an anhydrous alcohol ablation group (24 cases). Treatment outcomes were compared by analyzing the number of CT scans, effectiveness, and complications. Results: In the radiofrequency group, symptoms of bilateral hyperhidrosis significantly improved in 24 patients, with an 80% postoperative satisfaction rate. In the alcohol ablation group, symptoms significantly improved in 19 patients postoperatively, with a 79.2% satisfaction rate. There was no statistically significant difference in effectiveness or complications between the two groups (all P>0.05). The number of CT scans in the radiofrequency group was 4.60 ± 0.56 and 6.08 ± 0.28 in the alcohol group, showing a statistically significant difference (P<0.05).This study concluded that both percutaneous radiofrequency ablation and alcohol ablation are effective methods for hyperhidrosis treatment, with similar effectiveness and complication rates, but the radiofrequency ablation group required fewer CT scans.